2005
DOI: 10.1108/00330330510610591
|View full text |Cite
|
Sign up to set email alerts
|

Internet development and connectivity in Nigeria

Abstract: PurposeTo describe internet development and connectivity in Nigeria.Design/methodology/approachReviews the history of the internet in Africa, particularly in Nigeria, and surveys its current status.FindingsRecommendations are given on how use of the internet can be developed in Nigeria.Originality/valueIt will assist relevant authorities and stakeholders in Nigeria and in other developing countries to gain insights on how to improve internet connectivity. It also provides insights into the problems of developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 5 publications
1
33
0
Order By: Relevance
“…for a digital entrepreneur, the most important things are office space, internet and power, and in that regard, iDEA has provided the three basic things needed (P5: iDEA tenant). It is clearly evident that despite the fact that office space, electrical power and internet are indispensable resources for any digital entrepreneur, the Nigerian entrepreneurial environment suffers severely from the lack of these basic amenities (Adomi, 2005;Mohammed et al, 2013;Okafor, 2008). The deficiency of these environmental conversion factors can impede the translation of entrepreneurial desire, skills and knowledge into the functioning of running a successful tech business.…”
Section: Results and Analysis Of Empirical Findingsmentioning
confidence: 99%
“…for a digital entrepreneur, the most important things are office space, internet and power, and in that regard, iDEA has provided the three basic things needed (P5: iDEA tenant). It is clearly evident that despite the fact that office space, electrical power and internet are indispensable resources for any digital entrepreneur, the Nigerian entrepreneurial environment suffers severely from the lack of these basic amenities (Adomi, 2005;Mohammed et al, 2013;Okafor, 2008). The deficiency of these environmental conversion factors can impede the translation of entrepreneurial desire, skills and knowledge into the functioning of running a successful tech business.…”
Section: Results and Analysis Of Empirical Findingsmentioning
confidence: 99%
“…As pointed out by Aguolu (1996), since independence in 1960, there has been an unrelenting upsurge in the establishment of educational institutions at all levels, especially university education. And, the World Wide Web (WWW) became available in Nigeria in 1996, while full Internet services became available in 1998, and the number of NCC (Nigerian Communications Commission) licensed Internet service Providers rose to over 150 by 2001 (Adomi 2005). The library Web site continues to evolve as a gateway for providing Web-based library services to the students and university staffs.…”
Section: Introductionmentioning
confidence: 98%
“…Their findings revealed that lack of an adequate ICT infrastructure and affordable online access, absence of in-depth ICT skills and information searching skills among library staff and users are barriers to the use of electronic resources. In the same vein, Ondari-Okenwa (2004), Ashcroft and Watts (2005), Adomi (2005) and Oduwole and Sowole (2006) identified problems in the adoption and usage of ICT and electronic resources in Nigeria to include lack of adequate ICT skills among staff and users, low basic information literacy levels in the Nigerian population and prohibitive cost in developing countries to gain access to the Internet. The findings were corroborated by those of Salaam and Adegbore (2010) who studied Internet access and use by the students of private universities in Ogun State, Nigeria.…”
Section: Constraints To the Use Of Internet Resourcesmentioning
confidence: 99%